More On the Voicing of English Obstruents: Voicing Retention vs. Voicing Loss - Gonet, Wiktor; Święciński, Radosław (Research in Language, 2012)
In Gonet (2010), one of the present authors found out that English word-final phonologically voiced obstruents in the voicing-favouring environment exhibit asymmetrical, if not erratic, behaviour in that voicing in plosives is most often retained while in fricatives voicing retention concerns only about 1/3 of the cases, with the other possibilities (partial and complete devoicing) occurring in almost equal proportions. The present study is an attempt at exploring the intricacies of devoicing in English to examine to what extent the general tendency towards obstruent devoicing is overridden by voicing retention triggered by adjacent voiced segments both within words and across word boundaries. This study is based on a relatively large knowledge base obtained from recordings of spontaneous R. P. pronunciation.